ANALISIS STRATEGI BAURAN PEMASARAN PADA PERUSAHAAN PRODUKSI SUSU DAN MAKANAN DI ERA INDUSTRY 4.0 - Budiman, Rahma Nur Aulia; Anggraini, Rahma; Siboro, Muhammat Delisae; Susilowati, Isnurrini Hidayat (Jurnal Pariwisata Bisnis Digital dan Manajemen, 2024)
The Industrial Revolution 4.0 has driven a digital transformation that has brought significant changes across various sectors, including marketing. This study explores the marketing mix strategies employed by PT Cimory to address the challenges and opportunities of the Industry 4.0 era. With rapid technological advancements and the dynamic nature of consumer behavior, it is crucial for companies to adapt and innovate. This study aims to analyze how PT Cimory leverages the components of the marketing mix—product, price, place, and promotion—to enhance its market share and competitive advantage. The research adopts a qualitative design, utilizing secondary data from PT Cimory's annual reports, journal articles, and online media sources. The findings indicate that PT Cimory's strategic integration of technological advancements and innovative marketing approaches has significantly influenced consumer behavior and purchasing decisions, thereby strengthening its market position.